Tính Nhanh
3/2+3/6+3/12+3/20+3/30
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
ta có : (ghi lại đề)
=6+12+18+24+30/3+6+9+12+15
=2*(3/3+6/6+9/9+12/12+15/15)
=2*(1+1+1+1+1)
=2*5=10
chúc main học tốt nhé
\(\dfrac{3}{-4}+\dfrac{-3}{-4}+\dfrac{2}{5}+\dfrac{-1}{2}+\dfrac{3}{5}\\ =\left(\dfrac{-3}{4}+\dfrac{3}{4}\right)+\left(\dfrac{2}{5}+\dfrac{3}{5}\right)-\dfrac{1}{2}\\ =0+1-\dfrac{1}{2}\\ =1-\dfrac{1}{2}\\ =\dfrac{1}{2}\)
\(=\left(-\dfrac{3}{4}+\dfrac{3}{4}\right)+\left(\dfrac{2}{5}+\dfrac{3}{5}\right)-\dfrac{1}{2}=1-\dfrac{1}{2}=\dfrac{1}{2}\)
a: 14/5-7/5=7/5
b: 7/8-1/3+5/4
=21/24-8/24+30/24
=43/24
c; =7/6+5/6+2/15+13/15
=2+1
=3
d: =4*5/3*11=20/33
e: =2/9*1/6*1/4=2/9*1/24=1/108
2:
a: \(=\dfrac{3}{9}\cdot\dfrac{4}{4}\cdot\dfrac{5}{5}\cdot\dfrac{6}{6}\cdot\dfrac{7}{7}=\dfrac{1}{3}\)
b: \(=\dfrac{1}{6}\left(\dfrac{22}{3}-\dfrac{2}{3}\right)=\dfrac{10}{3}\cdot\dfrac{1}{6}=\dfrac{10}{18}=\dfrac{5}{9}\)
c; \(=\dfrac{1}{3}\left(9-\dfrac{2}{5}-\dfrac{3}{5}\right)=\dfrac{8}{3}\)
`1/2+2/4+3/6+4/8+5/10+6/12`
`=1/2+1/2+1/2+1/2+1/2+1/2`
`=1/2*6=3`
`1/3+1/4+1/5+8/10+20/15+20/30`
`=(1/3+1/4)+(1/5+4/5)+(4/3+2/3)`
`=7/12+1+2`
`=7/12+3=43/12`
\(\dfrac{1}{2}+\dfrac{2}{4}+\dfrac{3}{6}+\dfrac{4}{8}+\dfrac{5}{10}+\dfrac{6}{12}\)
\(=\dfrac{1}{2}+\dfrac{1}{2}+\dfrac{1}{2}+\dfrac{1}{2}+\dfrac{1}{2}+\dfrac{1}{2}\)
\(=\dfrac{1}{2}\times6=3\)
\(------\)
\(\dfrac{1}{3}+\dfrac{1}{4}+\dfrac{1}{5}+\dfrac{8}{10}+\dfrac{20}{15}+\dfrac{20}{30}\)
\(=\dfrac{1}{3}+\dfrac{1}{4}+\dfrac{1}{5}+\dfrac{4}{5}+\dfrac{4}{3}+\dfrac{2}{3}\)
\(=\left(\dfrac{1}{3}+\dfrac{4}{3}+\dfrac{2}{3}\right)+\left(\dfrac{1}{5}+\dfrac{4}{5}\right)+\dfrac{1}{4}\)
\(=\dfrac{7}{3}+1+\dfrac{1}{4}\)
\(=\dfrac{28}{12}+\dfrac{12}{12}+\dfrac{3}{12}\)
\(=\dfrac{43}{12}\)
\(\dfrac{3}{1\cdot3\cdot5}+\dfrac{3}{3\cdot5\cdot7}+\dfrac{3}{5\cdot7\cdot9}+\cdot\cdot\cdot+\dfrac{3}{37\cdot39\cdot41}\)
\(=\dfrac{3}{4}\left(\dfrac{4}{1\cdot3\cdot5}+\dfrac{4}{3\cdot5\cdot7}+\dfrac{4}{5\cdot7\cdot9}+\cdot\cdot\cdot+\dfrac{4}{37\cdot39\cdot41}\right)\)
\(=\dfrac{3}{4}\left(\dfrac{1}{1\cdot3}-\dfrac{1}{3\cdot5}+\dfrac{1}{3\cdot5}-\dfrac{1}{5\cdot7}+\dfrac{1}{5\cdot7}-\dfrac{1}{7\cdot9}+\cdot\cdot\cdot+\dfrac{1}{37\cdot39}-\dfrac{1}{39\cdot41}\right)\)
\(=\dfrac{3}{4}\left(\dfrac{1}{3}-\dfrac{1}{39\cdot41}\right)\)
\(=\dfrac{3}{4}\cdot\dfrac{532}{1599}=\dfrac{133}{533}\)
#Ayumu
12/18 + 12/42 = 2/3 + 2/7 = 14/21 + 6/21 = 20/21
1/2 + 2/4 + 3/6 + 4/8 + 5/10 + 6/12
= 1/2 + 1/2 + 1/2 + 1/2 + 1/2 + 1/2
= 1/2 x 6
=6/2
=3
3/2+3/6+3/12+3/20+3/30
=3/2+1/2+1/4+3/20+1/10
=30/20+10/20+5/20+3/20+2/20
=30+10+5+3+2/20
=50/20=5/2
\(\frac{3}{2}\)+\(\frac{3}{6}\)+\(\frac{3}{12}\)+ \(\frac{3}{20}\)+\(\frac{3}{30}\)
= \(\frac{3}{2}\) + \(\frac{1}{2}\)+ \(\frac{1}{4}\)+ \(\frac{3}{20}\)+ \(\frac{1}{10}\)
= \(\frac{30}{20}\)+ \(\frac{10}{20}\)+ \(\frac{5}{20}\)+\(\frac{3}{20}\)+\(\frac{2}{20}\)
= \(\frac{50}{20}\)= \(\frac{5}{2}\)